2015
DOI: 10.3109/07420528.2015.1079215
|View full text |Cite
|
Sign up to set email alerts
|

Acute and delayed responses of C-reactive protein, malondialdehyde and antioxidant markers after resistance training session in elite weightlifters: Effect of time of day

Abstract: The aim of this study was to investigate the effect of an Olympic-Weightlifting-session followed by 48-h recovery period on the oxidative and antioxidant parameters' diurnal variation. Nine weightlifters (21 ± 0.5 years) performed, in randomized order, three Olympic-Weightlifting-sessions at 08 h:00, 14 h:00 and 18 h:00. Blood samples were collected: at rest and 3 min and 48 h after each session. C-reactive protein (CRP), rate of lipid peroxidation and antioxidant activities were assessed. At rest, analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 58 publications
7
58
1
3
Order By: Relevance
“…These divergences between elite weightlifter and healthy sedentary subjects could be due to the training level of the subjects and the effect of training at a specific TOD (i.e., participants of the present study regularly trained between 15:30 and 17:30). In this context, Bloomer et al (7,8), Subudhi et al (40), and Ammar et al (2) indicated that being experienced resistance trained could result in a lower MDA and muscle damage levels. On the other hand, the previous studies suggest a link between the diurnal variation of the oxidative stress and the muscle damage markers (11,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These divergences between elite weightlifter and healthy sedentary subjects could be due to the training level of the subjects and the effect of training at a specific TOD (i.e., participants of the present study regularly trained between 15:30 and 17:30). In this context, Bloomer et al (7,8), Subudhi et al (40), and Ammar et al (2) indicated that being experienced resistance trained could result in a lower MDA and muscle damage levels. On the other hand, the previous studies suggest a link between the diurnal variation of the oxidative stress and the muscle damage markers (11,32).…”
Section: Discussionmentioning
confidence: 99%
“…1). Olympic exercises and training hours were chosen according to the peak and the minimum of circadian rhythm of anaerobic performances and with regard to the findings reported in the literature (2,3,16).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This exercise leads to an elevation of protein synthesis, activation of satellite cells, muscle cell signaling pathways and hormone responses [37]. Similarly, multiple physiological strain responses such as acute and delayed increases in muscle damage, oxidative stress and inflammation [20][21][22][23] have been also reported during strength exercise and particularly during Olympic weightlifting exercise. Therefore, weightlifting exercise, which is well known to elicit one of the highest peak power outputs and to requires high metabolic cost [38][39][40][41], was suggested to be the best exercise modality to test the efficacy of POM as an ergogenic and recovery aid supplementation during intensive exercise [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since POM supplementation has the potential to enhance physiological responses of people manifesting symptoms of physiological stress [5][6][7][8][9], and as intensive physical exercise is a potent and multifaceted physiological stressor [20][21][22][23], previous reports have suggested POM supplementation as an effective ergogenic and recovery aid for athletic populations [24,25]. The effectiveness of POM supplementation on exercise performance and post-exercise recovery has been shown by numerous studies [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%